A changing University - Martín Sabina, Elvira; Delgado Brito, Yeny (Atenas, 2016)
Higher Education is analyzed as part of the National Education System, from the social context in which its services are provided; a short historical briefing about the uprising of the university institutions in the western countries is delivered, and Cuban experience in different periods of its history. After accomplishing a long and complex path, undoubtedly the future will continue demanding from the Government, the academic community and the people committed to develop a better Cuban society, to continue their efforts with the unity and cooperation required to match the new challenges that has to be confronted in today’s world.